Information technology for development: from charity to sustainability - Guice, Jon; Eischen, Kyle (2002)
Jon Guice and Kyle Eischen argue that today the field of IT for development is characterized by non-commercial, non-technical efforts to apply standard technology in standard uses to new settings. If the field is to become a significant part of the wider IT industry, as some have advocated, there will have to be fundamental changes in the field, beginning with more basic and applied technical research. - Reproduced.
Keywords: Industry; Human development; Information technology